Unveiling femvertising: examining gratitude, consumers attitude towards femvertising and personality traits - Amber Waqar; Mahwish Jamil; Nabil Mohemmed AL-Hazmi; Aleena Amir (Cogent Business & Management, 2024)
The raised awareness of women's rights has resulted in their significant contribution to economic and societal advancement in the contemporary global paradigm. The promotion of female empowerment by various corporations has led to the emergence of femvertising as a significant trend in the media. The current research attempts to empirically examine the relationship between the message involvement of consumers and their attitude towards femvertising. The present study further investigates the potential mediating role of gratitude in the relationship between message involvement and attitude towards femvertising among consumers. Moreover, this study provides additional evidence supporting the notion that gratitude serves as a mediator in the association between feminist consciousness and attitude towards femvertising. In addition, the moderating influence of personality traits, specifically extraversion and agreeableness, on the indirect association between message involvement/feminist consciousness and attitude towards femvertising through the mediating mechanism of gratitude has been tested. The data collection process involved the utilization of a survey instrument, while the hypotheses were subjected to testing through the use of PROCESS macros for SPSS.
Keywords: 650; Femvertising; feministconsciousness; gratitude; message involvement; and personality traits